2019
DOI: 10.14202/vetworld.2019.1599-1607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with Ehrlichia infections in smallholder dairy cattle in Nairobi City County, Kenya

Abstract: Background and Aim: Ehrlichiosis caused by Ehrlichia ruminantium is a tick-borne disease of great economic importance in cattle production worldwide. Despite its economic impact, limited knowledge is available on its epidemiology in Africa, including Kenya. Suspected cases of E. ruminantium infections have been reported in the recent past to the University of Nairobi's Veterinary Hospital, prompting the need to investigate their possible re-emergence. Therefore, this study was aimed at determining the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…The study area and design have been described in detail previously [23]. This was a cross-sectional study undertaken between January and May 2017.…”
Section: Study Area and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The study area and design have been described in detail previously [23]. This was a cross-sectional study undertaken between January and May 2017.…”
Section: Study Area and Designmentioning
confidence: 99%
“…Previously, there had been clinical cases reported to the University of Nairobi Veterinary Hospital, Kenya presenting with unspecific clinical signs such as unthriftness and loss of body conditions. On screening of cattle from the areas where the clinical cases had originated, E. ruminantium was identified by antigen detection using Enzyme-linked Immunosorbent Assay (ELISA) [23]. Additionally, microscopic examination of blood from these cattle revealed that some of them had Ehrlichia-like inclusion bodies in the white blood cells suggesting infections with other unknown potentially pathogenic haemoparasites [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. ruminantium , initially named as Rickettsia ruminantium , was the first species of Ehrlichia to be discovered. E. ruminantium infected ruminants mainly in African areas such as Kenya and Uganda ( Allsopp, 2010 ; Peter et al, 2019 ; Tumwebaze et al, 2020 ), and in other areas like Northwest China ( Guo et al, 2018 ) and Oman ( El-Neweshy et al, 2019 ). However, E. ruminantium were also reported in free-living jaguars in Brazil ( Widmer et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports on animal anaplasmosis are available from France, Massachusetts, Brazil, Zambia Ethiopia and Kenya in both domestic and wild animals [17][18][19][20][21][22]. While Anaplasma in NHPs has been reported in some countries, its importance in NHPs in Kenya is not yet known which has therefore led us to investigate the occurrence of this bacteria in NHPs in Laikipia, Kenya.…”
Section: Introductionmentioning
confidence: 99%